Znak symboliczny w cyfrowej komunikacji - Kaźmierczak, Marek; Szczęsna, Ewa (Studia Europaea Gnesnensia, 2016)
The article concerns the rdations between digital and symbolic signs. Digital technology shapes the forms of functioning of symbolic signs in contemporary culture. Semiotics was the theoretical background for our research.